THE SIGNING OF INDONESIA-SINGAPORE FIR REALIGNMENT AGREEMENT 2022: PROSPECT FOR NEW INDONESIAN AIR DEFENSE IDENTIFICATION ZONE? - Naufal Faiz Muhammad (LPPM Universitas Ekasakti Padang, 2023)
Indonesia's location makes it vulnerable to border disputes and security threats. Indonesia needs to establish a universal Indonesian national defense system to defend its sovereignty and territorial integrity. One of them is in air defense. In order to identify foreign aircraft entering Indonesian airspace early and to provide security for the Indonesian Archipelagic Sea Lanes (ALKI), the establishment of ADIZ in the country's EEZ is a crucial and required subject. This has the potential to become a long-term prospect that can be maximized to meet Indonesia's air security needs. Even though establishing a new Indonesian ADIZ must still be halted because of the delegation of Natuna FIR under the Indonesia-Singapore FIR agreement 2022, the signing of this treaty has produced a new pattern in Indonesia's air defense strategy. Indonesia's air defense, which is still far from ideal, can actually develop after the signing of the FIR agreement. However, this also requires an evaluation of the long-term plan for air defense in Indonesia so that it can produce national sovereignty.